Working Paper 34: Local certification through Collective Action: An innovative approach to anti-corruption compliance and due diligence (Basel Institute on Governance Working Papers, 2021)
How can local certification of small and mid-sized enterprises (SMEs) help to alleviate anti-corruption due diligence for SMEs as well as multinational corporations (MNC) seeking to work with them. This Working Paper by the Basel Institute's Collective Action team attempts to answer that question based on discussions and analysis of current local certification initiatives in different countries and sectors.Local certification in this context means the assessment of a company’s anti-corruption compliance standards according to a method devised through a Collective Action and developed within a domestic (local) market. The local component also involves verification (certification) by a reputable organisation based in the same country as the entity that is being certified. The paper explores:Due diligence dilemmas faced by both SMEs and MNCs.How local certification can help SMEs develop and demonstrate robust anti-corruption compliance procedures.How a trusted certification programme can help alleviate due diligence on third parties by MNCs, using a risk-based approach.Wider benefits, including raising standards of compliance across the board.How a Collective Action approach boosts the potential of local certification to achieve these wins.Special considerations and six practical recommendations for practitioners seeking to raise levels of anti-corruption compliance through a local certification scheme.